Recent Advances in the Biology, Therapy and Management of Melanoma - Davids, Lester M. (IntechOpen, 2013)
The book Recent Advances in the Biology, Therapy and Management of Melanoma brings up-to-date information regarding a number of aspects which culminate in illuminating potential targets in the fight against melanoma. This book is intended to be a reference book for both the scientific and clinical communities and brings complicated subject matter together in an easy, readable way. Undoubtedly fundamental scientific understanding has to then be translated to the clinic in order for us to make significant strides in eradicating melanoma. It is hoped that scientists, clinicians, students and residents find this book useful in their studies on melanoma and that it not only expands their perspectives and views on the field, but challenges them to forge ahead towards discovering the ultimate cure.